Integrated molecular network and HPLC‐UV‐FLD analysis to explore antioxidant ingredients in camellia nitidissima Chi. Issue 4 (17th March 2021) - Cheng, Chuan‐jing; Hou, Xiao‐tao; Hao, Er‐wei; Palachai, Nut; Wattanathorn, Jintanaporn; Bai, Gang; Hou, Yuan‐yuan
Abstract : Abstract: At present, screening of active ingredients from natural products for pharmacological and clinical research is mostly time‐consuming and costly. In this study, a molecular network (MN) guided high performance liquid chromatography‐ultraviolet‐fluorescence detector (HPLC‐UV‐FLD) method was carried out to profile the global antioxidant activity compounds, including the trace amount ingredients in Camellia nitidissima Chi (CNC). Firstly, HPLC‐UV‐FLD postcolumn derivatization system was utilized to screen the antioxidants. Then the MN of CNC was established via mass spectrometry (MS) data for getting the connection between ingredient structures. As a result, HPLC‐UV‐FLD indicated three antioxidant ingredients: gallic acid (126.3 mg/g), catechin (564.8 mg/g), and salicylic acid (24.3 mg/g). Combined with the MN, the actives' precise location and connection relationship were clarified based on the structural similarities. A new antioxidant ingredient, okicamelliaside, was suggested and evaluated at free radical scavenging and enzymatic protection. The novel method of activity and structural correlation analysis based on MN could provide a useful guide for screening trace active ingredients in natural products. Practical Application: Three main ingredients were screened out from Camellia nitidissima Chi by HPLC‐UV‐FLD postcolumn derivatization system. Integrated molecular network and HPLC‐UV‐FLD analysis, a new type of antioxidant okicamelliaside was selected. The novel method of activity and structural correlation analysis based on molecular network could provide a useful guide for screening trace active ingredients in natural products.